Application of a vane-recessed turbular-passage casing treatment to a multistage axial-flow compressor - Akhlaghi, M (Cranfield University, 2001)
The current study investigates a range of issues relating to the use of a vane-recessed tubular-passage casing treatment as a passive stall control technique in a multistage axial-flow compressor. The focus of the research was to determine whether such a treatment could delay the initiation of stall at lower mass flow rates as well as providing the most beneficial improvement in flow characteristics without sacrificing compressor efficiencies. Specific objectives of this study were to examine possible improvements or deterioration in the flow characteristics including stall margin, peak pressure rise coefficients and maximum efficiency in a multistage axial flow compressor. A casing treatment in addition to several spacer rings was developed from two initial designs and tested on the first stage of a low speed three-stage axial-flow compressor with a (0.7) hub to tip diameter ratio. The treatment configuration consisted of three parts: an outer casing ring, with a tubular shaped passage on the inside diameter, a set of 120 evenly spaced curved vanes, and a shroud or inner ring. The casing treatment was positioned following the inlet guide vanes upstream and partly covering the tip of the rotor blades. The main parts of the casing treatment including the recessed vanes in addition to some of the spacer rings were manufactured from high quality acrylic. Eight additional spacer rings of various shapes and geometry were added. The first ring held and partly covered the IGVs, in front of the casing treatment. The rotor tip exposure ratio was thought to have a significant impact on the effectiveness of the casing treatment. Therefore the other seven rings were used to provide the desired uncovered region of the rotor tip axial chord of about 10% in order to provide a range of exposures of (23.2%, 33.3%, 43.4%, 53.5%, 63.6%, 73.7%, and 83.8%). The results showed significant improvements in stall margin in all treated casing configurations along with insignificant efficiency sacrifices in some compressor builds. About (28.56%) of stall margin improvement in terms of corrected mass flow rate was achieved using a casing treatment with a (33.3%) rotor tip exposure. The compressor build with (0.535) rotor exposure ratios was the best configuration in terms of efficiency gain and loss characteristics. This build was able to provide the highest values of the maximum efficiencies in comparison with the performance achieved from the solid casing. An improvement of (1.81%) in the maximum efficiency in terms of the overall total-total pressure ratio, in association with a (22.54%) stall margin improvement in terms of the corrected mass flow rates were achieved by the application of this treatment configuration. The improvement in the peak pressure rise coefficients in terms of the overall total-total pressure ratio, obtained from this build was (2.33%). The compressor configuration using a casing treatment with a (0.636) rotor exposure ratio was the best build in terms of the pressure rise coefficients. This configuration was able to provide highest value of the peak pressure rise in comparison with the characteristics achieved from the datum build. An improvement of (2.65%) in the peak pressure rise coefficient in terms of the overall total-total pressure ratio, in association with a (22.49%) improvement in stall margin in terms of the corrected mass flow rates was achieved from this casing treatment build. The improvement in maximum efficiency in terms of the overall total-total pressure ratio, obtained from this build was (1.03%). The results suggest that the vane-recessed tubular-passage casing treatment designed as part of this investigation achieved the objectives, which were established for the research. In the majority of instances it not only produced gains in flow range, pressure rise coefficients and efficiencies, but also enabled the rotating stall, which developed at much lower mass flow rates in the compressor, to become progressive rather than abrupt.